2020
DOI: 10.2105/ajph.2019.305461
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Surveillance With Twitter Data: Emerging Topics and Social Bots

Abstract: Objectives. To use publicly accessible data from people who post to Twitter to rapidly capture and describe the public’s recent experiences with cannabis. Methods. We obtained Twitter posts containing cannabis-related terms from May 1, 2018, to December 31, 2018. We used methods to distinguish between posts from social bots and nonbots. We used text classifiers to identify topics in posts (n = 60 861). Results. Prevalent topics of posts included using cannabis with mentions of cannabis initiation, processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 29 publications
(40 reference statements)
6
69
0
Order By: Relevance
“…The content analysis done on the US data set revealed some similar themes to previous content analyses such as current use and legalization, transactions, medical use, and the cannabis industry [ 13 , 24 ]; however, our analysis also presented new themes not uncovered in previous content analyses including the topics about the scent of cannabis and places that people use, and medical use and the cannabis industry. Our analysis did not detect several of the themes that other authors did, such as romance, tobacco, and friendship [ 15 ] or processed product use, cannabidiol and hemp use, and polysubstance use [ 24 ]. This could be because previous content analyses were conducted primarily with influential Twitter users, with adolescent users, and not with all available tweets [ 12 , 13 , 15 , 23 ] or because of a more expansive time frame and fewer geographic restrictions than other studies [ 24 ].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The content analysis done on the US data set revealed some similar themes to previous content analyses such as current use and legalization, transactions, medical use, and the cannabis industry [ 13 , 24 ]; however, our analysis also presented new themes not uncovered in previous content analyses including the topics about the scent of cannabis and places that people use, and medical use and the cannabis industry. Our analysis did not detect several of the themes that other authors did, such as romance, tobacco, and friendship [ 15 ] or processed product use, cannabidiol and hemp use, and polysubstance use [ 24 ]. This could be because previous content analyses were conducted primarily with influential Twitter users, with adolescent users, and not with all available tweets [ 12 , 13 , 15 , 23 ] or because of a more expansive time frame and fewer geographic restrictions than other studies [ 24 ].…”
Section: Discussionsupporting
confidence: 66%
“…Our analysis did not detect several of the themes that other authors did, such as romance, tobacco, and friendship [ 15 ] or processed product use, cannabidiol and hemp use, and polysubstance use [ 24 ]. This could be because previous content analyses were conducted primarily with influential Twitter users, with adolescent users, and not with all available tweets [ 12 , 13 , 15 , 23 ] or because of a more expansive time frame and fewer geographic restrictions than other studies [ 24 ].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In March, the FDA began responding to unsupported therapeutic claims about CBD and novel coronavirus disease 2019 (COVID-19) by sending more strongly worded warning letters that instruct recipients to withdraw such claims within 48 hours [1]. The FDA has limited regulatory capacity to police the numerous CBD retailers and the even larger number of unsupported therapeutic claims about CBD and other cannabis-derived products, so it is worth considering whether this is an efficient, high-impact strategy [2,3].…”
Section: Editorialmentioning
confidence: 99%
“…Since then, Allem has shown that tweets generated by bots are twice as likely as their real counterparts to attest that e-cigarettes help people to give up smoking 1 . Bots are also more likely to tout the unproven health benefits of cannabis 2 . These studies rely on algorithms that estimate the likelihood that a Twitter account is automated.…”
mentioning
confidence: 99%